Mental Health Anak Dan Remaja Palestina di Tengah Konflik: Analisis Dampak dan Intervensi - Hasana, Fauziatul; Syarif, Nurul Hidayanti; Suhaeb, Firdaus W. (Lembaga Intelektual Muda Maluku, 2025)
The prolonged conflict in Palestine has had a serious impact on the mental health of children and adolescents. The amount of violence, loss and instability of life triggers disorders such as trauma, depression and depression. This article analyzes the psychological impact of conflict and evaluates interventions that have been implemented, such as psychosocial support programs, trauma therapy and community-based approaches. The data of this research article was obtained from various sources in the Journal and the Google Scholar database. The data analysis technique used, namely qualitative data analysis, consists of data reduction, data presentation, and conclusion drawn. The findings of the article suggest that sustained and culturally sensitive interventions are important for improving children's mental resilience. Through a review of literature and field data from various humanitarian organizations, exposure to violence, loss of family members, displacement, and future uncertainty triggers psychological disorders such as PTSD, anxiety, depression, and behavioral disorders. On the other hand, community-based interventions, psychosocial support programs in schools, and family involvement in the recovery process have been proven to provide positive results in increasing children's resilience. This research emphasizes the importance of a holistic and sustainable approach to addressing the mental health of children and adolescents in conflict zones, as well as the need for stronger international support to ensure access to safe and decent mental health services